Social Change and Health Status in Prehispanic Northwest Argentina (Quebrada de Humahuaca, Jujuy) ca. 500-1550 AD - Gheggi, María Soledad (2014)
The effects of social, political and economic changes on the health and lifestyle of past populations from Quebrada de Humahuaca (Jujuy, Argentina) ca. 500- 1550 AD are approached through the study of bioarchaeological indicators of nutritional and functional stress, trauma, infections and dental pathologies in a sample of human bone remains (N=134). Although crude frequencies of pathologies varied, only changes in functional stress markers proved to be statistically significant, indicating that populations engaged in heavier labor force over time. This result can be related to the trend toward labor intensification seen in the archaeological record. Metabolic stress indicators increased between the Early Regional Development Period (ca. 900-1250 AD) and Late Regional Development Period (ca. 1250- 1430 AD), possibly related to the concentration of population in dense nucleated settlements. No change in oral pathologies related to diet were seen, suggesting that diet change little over time. Variations in trauma frequencies were not significant either, contrary to the idea of an escalation of conflict during the Late Regional Development Period as indicated from other archaeological indicators. Our results serve both to confront models developed from the archaeological record and to complement them with biological data indicating that further analysis is required, especially in finer temporal units.